The performance optimization video collection. - Bevacqua, Nicolas; Everts, Tammy; Hales, Wesley; Safari eBooks; O'Reilly Fluent Web Platform Conference (2016 : San Francisco, California) ([Place of publication not identified] : O'Reilly, 2016)
"Even as computers have grown faster, the Web has grown heavier. Seemingly trivial differences in load time and responsiveness can make a huge difference in user response. These talks help you prioritize performance, integrate it with your development process, and make users happy."--Resource description page.
High performance in the critical rendering path / Nicolas Bevacqua -- How slow load times hurt the user experience (and ultimately your bottom line) / Tammy Everts -- Owning web performance with PhantomJS and Docker / Wesley Hales.
Presenters, Nicolas Bevacqua, Tammy Everts, Wesley Hales.
Title and publication information from resource description page (Safari, viewed August 10, 2016).
Selected videos from the O'Reilly Fluent Web Platform Conference: March 7-10, 2016, San Francisco, CA.
Keywords: Internet programming; JavaScript (Computer program language); HTML (Document markup language); Application software -- Development; Electronic books